2023
DOI: 10.1097/coh.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

Delivery platforms for broadly neutralizing antibodies

Abstract: Purpose of reviewPassive administration of broadly neutralizing antibodies (bNAbs) is being evaluated as a therapeutic approach to prevent or treat HIV infections. However, a number of challenges face the widespread implementation of passive transfer for HIV. To reduce the need of recurrent administrations of bNAbs, gene-based delivery approaches have been developed which overcome the limitations of passive transfer.Recent findingsThe use of DNA and mRNA for the delivery of bNAbs has made significant progress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…The antibodies encoded by nucleic acids can be produced rapidly and are likely to be produced commercially at a much lower cost than equivalent protein therapies . Researchers are already exploring the possibility of using antibodies encoded by nucleic acids to treat and prevent infectious diseases. , For decades, with the development of lipid nanoparticle (LNP) delivery systems, mRNA platforms have evolved from a theoretical idea to a clinical reality . Encapsulation of nucleoside-modified mRNA in LNP has also proven to be an effective tool for producing target proteins .…”
Section: Introductionmentioning
confidence: 99%
“…The antibodies encoded by nucleic acids can be produced rapidly and are likely to be produced commercially at a much lower cost than equivalent protein therapies . Researchers are already exploring the possibility of using antibodies encoded by nucleic acids to treat and prevent infectious diseases. , For decades, with the development of lipid nanoparticle (LNP) delivery systems, mRNA platforms have evolved from a theoretical idea to a clinical reality . Encapsulation of nucleoside-modified mRNA in LNP has also proven to be an effective tool for producing target proteins .…”
Section: Introductionmentioning
confidence: 99%
“…One promising method for sustained delivery of bNAbs is through AAV-mediated delivery of antibody expression cassettes, known as vectored immunoprophylaxis. [20][21][22][23][24][25] Trials in mice, macaques, and recently humans have demonstrated the potential of this strategy for sustained secretion of therapeutic anti-HIV-1 antibodies. However, pre-existing immunity against AAV vectors, low levels of antibody secretion, uncertainty regarding long-term expression, and seroconversion preventing re-dosing remain challenges limiting this approach.…”
mentioning
confidence: 99%